Professional burnout syndrome in a group of nursing staff employed in a psychiatric hospital - Tomaszewska, Katarzyna; Porczak, Waldemar; Guty, Edyta; Majchrowicz, Bożena (Journal of Education, Health and Sport, 2023)
Nurses are one of the occupational groups most exposed to stress in the health care system. In their daily work, the staff of a psychiatric ward often encounters threats, aggression or unpredictability of patients’ behavior. Employees, including nurses, often feel discomfort related to the treatment of patients admitted against their will, the need to use direct coercion. In psychiatry, it is also burdensome to participate in family matters of patients, to solve their problems. The group of factors recognized as stressful and causing psychological burden for nurses includes a large number of patients under their care, their serious condition as well as physical and verbal aggression of the patient and violence. The aim of the study was to present the problem of occupational burnout in a group of nursing staff employed in a psychiatric hospital Material and methods 203 nurses participated in the study. The research tool was a proprietary questionnaire and a standardized tool, the Ch. Maslach. The level of statistical significance in this study was p<0.05. Results The average occupational burnout rate was 34.9% ± 20.9%. Emotional exhaustion was assessed at 32.5% ± 28.5%, the level of depersonalization at 23.1% ± 26.1%. The main motivators in the work of nurses are earnings (57.3%), willingness to help others (54.4%) and a good atmosphere at work (35%). Conclusions: Mental burden in the work of a psychiatric nurse results in the development of occupational stress leading to occupational burnout. Actions are recommended to counteract the professional burnout syndrome